Autograph letter signed by Hermann Scherchen - Scherchen, Hermann, 1891-1966:::Creator:::::::::::: (2021)
Autograph letter signed from Hermann Scherchen to "Leonore" quoting lines and mentioning the addressee's involvement in Beethoven's opera Fidelio.